Insect metamorphosis : from egg to adult - Goor, Ron.; Goor, Nancy (New York : Atheneum, 1990)
Explains how insects grow, describing the various stages of incomplete and complete metamorphosis.
Includes index.
Wilson's Children.
Elem. School Library Collection.
School Library Journal.
4.6
3-6
Keywords: Insects -- Metamorphosis -- Juvenile literature; Insects -- Metamorphosis; Insects; Insects -- Metamorphosis